Effect of Health Intervention via Web-Based Education on Improving Information-Motivation-Behavioral Skills Related to HPV Vaccination Among Chinese Female College Students - Hong Wang; Xiaoyang Wang; Peipei Chen; Huifang Xu; Yin Liu; Ruihua Kang; Liyang Zheng; Xingyuan Sun; Xibin Sun; Shaokai Zhang (Frontiers Media S.A., 2023)
Objectives: The human papillomavirus (HPV) vaccination rate is generally low in China. This study aimed to assess the effect of web-based education on improving information-motivation-behavior skills related to HPV vaccination among Chinese female college students.Methods: From February to May 2020, female students were recruited from a university and divided into intervention and control groups. The intervention group received 7 days of HPV-related web-based education. Related information were collected using questionnaires in the baseline, 7 days, 1 month, and 3 months after the intervention. Chi-square test and repeated ANOVA were used to compare the differences between the two groups in the four surveys.Results: A total of 449 students (235 in the intervention and 214 in the control group) were included in the analysis. There were no statistical differences in demographic information between the two groups. Compared with the control group, students in the intervention group showed a richer knowledge and subjective norms of HPV vaccination (p < 0.05).Conclusion: The study provides preliminary support for a health intervention via web-based education in increasing HPV vaccination information among female college students.